forked from grahaminn/SICP
-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathex1-13.txt
53 lines (31 loc) · 1.45 KB
/
ex1-13.txt
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
To demonstrate:
Fib(n) = ((expt Φ n) - (expt Ψ n)) / (sqrt 5)
We know that:
Fib(n) = 0 n = 0
1 n = 1
Fib(n-1) + Fib(n-2)
---------------------------------------
For n = 0
(1-1) / (sqrt 5) = 0 / sqrt(5) = 0
For n = 1
((expt Φ 1) - (expt Ψ 1)) / (sqrt 5) =(((1 + (sqrt 5)) / 2) - ((1 - (sqrt 5)) / 2)) / (sqrt 5) = 1
Assume the following are true:
Fib(n) = ((expt Φ n) - (expt Ψ n)) / (sqrt 5)
Fib(n-1) = ((expt Φ n-1) - (expt Ψ n-1)) / (sqrt 5)
Prove that:
Fib(n+1) = ((expt Φ n+1) - (expt Ψ n+1)) / (sqrt 5)
----------------------------------------
Fib(n+1) = Fib(n) + Fib(n-1)
Fib(n+1) = (((expt Φ n) - (expt Ψ n)) / (sqrt 5)) + (((expt Φ n-1) - (expt Ψ n-1)) / (sqrt 5))
= (((expt Φ n) - (expt Ψ n)) + ((expt Φ n-1) - (expt Ψ n-1))) / (sqrt 5)
= ((expt Φ n) - (expt Ψ n) + (expt Φ n-1) - (expt Ψ n-1)) / (sqrt 5)
= (((expt Φ n) + (expt Φ n-1)) + ((expt Ψ n) + (expt Ψ n-1))) / (sqrt 5)
= (((expt Φ n+1) * ((expt Φ -1) + (expt Φ -2))) - ((expt Ψ n+1) * ((expt Ψ -1) + (expt Ψ -2)))) / (sqrt 5)
= (((expt Φ n+1) * (expt Φ -1) * (1 + (expt Φ -1))) - ((expt Ψ n+1) * (expt Ψ -1) * (1 + (expt Ψ -1)))) / (sqrt 5)
considering that
1 + (expt Φ -1) = Φ
and
1 + (expt Ψ -1) = Ψ
= (((expt Φ n+1) * (expt Φ -1) * Φ) - ((expt Ψ n+1) * (expt Ψ -1) * Ψ)) / (sqrt 5)
= ((expt Φ n+1) - (expt Ψ n+1)) / (sqrt 5)
proved